Sidestream cigarette smoke effects on cardiovascular responses in conscious rats: involvement of oxidative stress in the fourth cerebral ventricle - Valenti, Vitor Engrácia [UNESP]; Abreu, Luiz Carlos de [UNESP]; Sato, Monica A.; Ferreira, Celso; Adami, Fernando; Fonseca, Fernando L. A.; Xavier, Valdelias; Godoy, Moacir; Monteiro, Carlos B.; Vanderlei, Luiz Carlos M. [UNESP]; Saldiva, Paulo H. N. (Biomed Central Ltd., 2012)
Background: Cigarette exposure increases brain oxidative stress. The literature showed that increased brain oxidative stress affects cardiovascular regulation. However, no previous study investigated the involvement of brain oxidative stress in animals exposed to cigarette and its relationship with cardiovascular regulation. We aimed to evaluate the effects of central catalase inhibition on baroreflex and cardiovascular responses in rats exposed to sidestream cigarette smoke (SSCS).Methods: We evaluated males Wistar rats (320-370 g), which were implanted with a stainless steel guide cannula into the fourth cerebral ventricle (4th V). Femoral artery and vein were cannulated for mean arterial pressure (MAP) and heart rate (HR) measurement and drug infusion, respectively. Rats were exposed to SSCS during three weeks, 180 minutes, 5 days/week (CO: 100-300 ppm). Baroreflex was tested with a pressor dose of phenylephrine (PHE, 8 mu g/kg, bolus) to induce bradycardic reflex and a depressor dose of sodium nitroprusside (SNP, 50 mu g/kg, bolus) to induce tachycardic reflex. Cardiovascular responses were evaluated before, 5, 15, 30 and 60 minutes after 3-amino-1,2,4-triazole (ATZ, catalase inhibitor, 0.001 g/100 mu L) injection into the 4th V.Results: Central catalase inhibition increased basal HR in the control group during the first 5 minutes. SSCS exposure increased basal HR and attenuated bradycardic peak during the first 15 minutes.Conclusion: We suggest that SSCS exposure affects cardiovascular regulation through its influence on catalase activity.